Promising new wing concepts for more efficient air transport. (Research'eu results magazine)
An EU initiative has advanced aircraft lifting technology beyond the state of the art. Modelling and design tools, novel configurations and wind tunnel test procedures should speed up commercialisation of greener aircraft.